Location and function of intrahepatic shunts in anaesthetised rats. Issue 9 (11th August 2003) - Li, X; Benjamin, I S; Naftalin, R; Alexander, B
Abstract : Background: In the present study we determined the proportion of shunt flow due to patent intrahepatic portal systemic shunts in the normal rat liver and its relationship with microsphere induced portal hypertension. Methods: Systemic and hepatic haemodynamics were measured continuously before, during, and after intraportal injection of 15 μm diameter microspheres in anaesthetised male Wistar rats. Functional hepatic blood flow and intrahepatic shunt flow were determined by the use of constant intraportal infusion of sorbitol and simultaneous measurements in the portal vein, hepatic vein, and carotid artery. The percentage of large shunts of diameter >15 μm were estimated by intraportal injection of 51 Cr labelled 15 μm diameter microspheres. Results: Hepatic sorbitol uptake was 97.9 (0.5)% in normal control rats, with functional hepatic blood flow equalling total hepatic blood flow (2.52 (0.23) ml/min/100 g body weight). Microsphere injection decreased sorbitol uptake to 12.8 (4.3)% and further to 4.1 (0.7)% when followed by hepatic arterial ligation. In the latter two groups, intrahepatic shunt flow (1.46 (0.15) and 1.16 (0.19) ml/min/100 g body weight, respectively) was not significantly different from portal venous flow (1.36 (0.20) and 1.20 (0.20) ml/min/100 g body weight, respectively). Portal venous flow remained at 70% of basal values and portal venous pressure only increased by 50% from baseline. 51 Cr labelled microsphere shunt fraction through large shunts (>15 μm) was less than 1.0%. Conclusion: The site of confluence between the hepatic artery and portal vein is in zone II. Intrahepatic shunts originate in presinusoidal regions in zone I in the normal liver and, when activated by intraportal injection of microspheres, divert 70% of the total portal blood flow away from zone III and thereby reduce acute increases in portal venous pressure.